Prognostic factors for remission in early rheumatoid arthritis: a multiparameter prospective study. Issue 6 (12th May 2004) - Gossec, L; Dougados, M; Goupille, P; Cantagrel, A; Sibilia, J; Meyer, O; Sany, J; Daurès, J-P; Combe, B
Abstract : Objective: To determine prognostic factors for remission in early rheumatoid arthritis. Methods: 191 patients with rheumatoid arthritis whose disease duration was less than one year were followed up prospectively for five years. Remission, defined by a disease activity score (DAS) of <1.6, was used as the outcome measure. Baseline clinical, laboratory, genetic, and radiographic data (with radiographic scores determined by Sharp's method, modified by van der Heijde) were obtained. Results: 48 patients (25.1%) fulfilled the remission criteria at the three year follow up visit, and 30 (15.7%) at three and five years. On univariate analysis by Fisher's exact test, remission at three years and persistent remission at five years were closely correlated with baseline DAS values, C reactive protein level, Ritchie score, health assessment questionnaire score, duration of morning stiffness, and to a lesser extent baseline total radiological scores and rheumatoid factor negativity. No significant correlation was found with sex, age, extra-articular manifestations, erythrocyte sedimentation rate, anti-cyclic citrullinated protein antibodies, anti-keratin antibodies, anti-HSP 90, anticalpastatin antibodies, antinuclear antibodies, or HLA-DRB1* genotypes. Logistic regression analysis showed that the baseline independent variables predictive of remission were low DAS, Ritchie score, morning stiffness duration, and total radiographic score. Conclusions: Baseline prognostic factors for remission in early rheumatoid arthritis were mainly clinical markers of disease activity and radiological scores.